Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Pemberian Imunisasi Tetanus Toksoid Di Wilayah Kerja Puskesmas Jontor Kota Subulussalam Tahun 2022 - Turipah Turipah; Lidya Natalia Sinuhaji; Edy Marjuang Purba; Anna Waris Nainggolan (Jurnal Kesehatan dan Fisioterapi, 2023)
Based on a 2018 report from the Ministry of Health, the coverage of TT immunization in Indonesia is still quite low (23.4%). Public awareness, especially pregnant women, to carry out Tetanus Toxoid Immunization is still low, this can be seen by the low coverage of Tetanus Toxoid immunization. For the work area of the Jontor Health Center, Subulussalam City, in 2021 there will be 226 pregnant women who will have TT1 immunization. The purpose of this study was to determine the relationship between the knowledge and attitudes of pregnant women and the administration of tetanus toxoid immunization in the work area of the Jontor Health Center, Subulussalam City in 2022. This type of research is an analytic observational study using a cross sectional approach. The total population obtained was 178 people who lived at the Jontor Health Center in Subulussalam City in 2022. The sample was based on the sample size formula of 42 people. Samples were obtained using a simple random side. Bivariate data analysis was carried out using a statistical test using chi-square, to see a relationship between the independent variables and the dependent variable with a degree of significance α = 0.05. There is a relationship between knowledge (p=0.027) and attitude (p=0.027) with the provision of TT immunization in the Work Area of the Jontor Health Center, Subulussalam City in 2022. It is suggested to the Health Center, to increase the promotive function of Tetanus Toxoid immunization to be able to increase pregnant women's knowledge related to giving Tetanus Toxoid Immunization and tetanus disease.Keywords: Tetanus toxoid, knowledge, attitudes